2014
DOI: 10.1016/j.molonc.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel resistance increases oncolytic adenovirus efficacy via upregulated CAR expression and dysfunctional cell cycle control

Abstract: Resistance to paclitaxel chemotherapy frequently develops in ovarian cancer. Oncolytic adenoviruses are a novel therapy for human malignancies that are being evaluated in early phase trials. However, there are no reliable predictive biomarkers for oncolytic adenovirus activity in ovarian cancer. We investigated the link between paclitaxel resistance and oncolytic adenovirus activity using established ovarian cancer cell line models, xenografts with de novo paclitaxel resistance and tumour samples from two sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…However, following iso-infection with dl922-947, there were significantly greater increases in both ÎłH2AX positivity and >4N DNA in PEO4 ( Fig. 2A), consistent with our previous observations that virus-induced DNA damage correlates with sensitivity (22,30).…”
Section: Adenovirus Dna Replication Triggers the Dna Damage Response supporting
confidence: 92%
See 1 more Smart Citation
“…However, following iso-infection with dl922-947, there were significantly greater increases in both ÎłH2AX positivity and >4N DNA in PEO4 ( Fig. 2A), consistent with our previous observations that virus-induced DNA damage correlates with sensitivity (22,30).…”
Section: Adenovirus Dna Replication Triggers the Dna Damage Response supporting
confidence: 92%
“…We have recently shown that oncolytic adenoviruses may be more effective in ovarian cancers with paclitaxel resistance (30). Data here show that these viruses may also have specific activity in another group of poor prognosis ovarian cancers, namely those with platinum and PARP inhibitor resistance thought intact HR function.…”
Section: Europe Pmc Funders Author Manuscriptsmentioning
confidence: 60%
“…4, 5 However, the therapeutic efficacy of paclitaxel is limited, with response rates between 29–63% because of chemoresistance. 4, 5, 6 Paclitaxel resistance is caused by several mechanisms, including overexpression of P-glycoprotein or other drug efflux pumps, 7, 8 alterations to microtubules involved in drug-binding or altered expression of tubulin isotypes and microtubule-associated proteins, 9, 10, 11 alterations to cell cycle and cell survival pathways 12, 13, 14 and the induction of treatment-related autophagy. 15, 16, 17 However, the molecular mechanisms by which resistance to paclitaxel occurs are not fully understood and further investigation is required.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated this possibility with the synergistic interaction between paclitaxel and roscovitine as well as PHA767491, two compounds known to affect DNA replication origins. Other smallmolecule inhibitors with overlapping mechanisms, namely CINK4, flavopiridol, PD-0332991 and purvalanol, have previously been shown to enhance taxane cytotoxicity or reverse taxane resistance (Zhang et al, 2013;Ingemarsdotter et al, 2015;Bible and Kaufmann, 1997;O'Connor et al, 2002). As such a co-targeting strategy is schedule dependent in most cases, the challenge would be to identify optimum dosing regimens that could yield maximal efficacy and minimal toxicity (Jackson et al, 2007;Shah and Schwartz, 2001).…”
Section: Discussionmentioning
confidence: 99%